Sabiá Virus–Like Mammarenavirus in Patient with Fatal Hemorrhagic Fever, Brazil, 2020 - de Mello Malta, Fernanda (Emerg Infect Dis, 2020)
New World arenaviruses can cause chronic infection in rodents and hemorrhagic fever in humans. We identified a Sabiá virus–like mammarenavirus in a patient with fatal hemorrhagic fever from São Paulo, Brazil. The virus was detected through virome enrichment and metagenomic next-generation sequencing technology.